(untitled) (The Review of Diabetic Studies, 2025)
Background: Irritable bowel syndrome (IBS) is a common disorder in primary care, where family physicians play a central role in management. Their knowledge of evidence-based dietary and pharmacological strategies is crucial for effective patient care and outcomes. Methods: A cross-sectional study was conducted using a self-administered questionnaire distributed to 142 practicing family physicians. The survey assessed demographic characteristics, knowledge of dietary management (including trigger foods and the low-FODMAP diet), and familiarity with pharmacological treatments for IBS. Results: Participants demonstrated moderate knowledge overall. While most physicians could identify common food triggers (71.1%) and first-line medications like antispasmodics (78.9%), significant gaps were identified. Only 40.8% understood low-FODMAP diet principles, and confidence in providing independent dietary counseling was low (32.4%). Knowledge of adjunctive therapies was also limited, with low recognition of the role of probiotics (48.6%) and low-dose antidepressants for pain modulation (36.6%). Conclusion: Family physicians possess a foundational understanding of IBS management but lack knowledge in advanced dietary strategies and newer pharmacological options. The findings highlight a need for targeted continuing medical education and interdisciplinary collaboration to bridge these knowledge gaps, improve patient outcomes, and optimize primary care for IBS.